PERSPEKTIF MASYARAKAT DESA KEMADUH BARON NGANJUK TENTANG RELEVANSI NAFKAH SUAMI TERHADAP KEHARMONISAN RUMAH TANGGA - Maryam Qurotul Aini, Siti; Hayati, Afiatul (USRATUNA: Jurnal Hukum Keluarga Islam, 2021)
The issue of livelihood is crucial in building household harmony. The husband is obliged to provide for his family with ma'ruf. This can create harmony in the household that is built.The people of Kemaduh Baron Nganjuk village have various views on the relevance of husband's livelihood to household harmony. This paper is the result of field research on this matter. This analytical descriptive research uses a qualitative approach, with data collection methods in the form of observation, interviews, and documentation. The results of the study reveal that the husband's livelihood from the perspective of the Kemaduh Baron Nganjuk village community is a gift from a husband to his wife in the form of money, to meet daily needs, which is in line with Amir Syaifuddin's opinion that the husband's income is shopping for food needs which includes basic materials such as clothing and housing. or clothing, food, and shelter. Meanwhile, their perspective on household harmony is the attitude of helping each other, pouring out their hearts (deliberations), the lack of debate in running the household with mutual understanding. This is in line with the theory of household harmony with the realization of the wishes of husband and wife, minimizing interpersonal conflicts, the realization of reciprocity between husband and wife in carrying out their respective obligations. According to the people of Kemaduh village, husband's livelihood and household harmony are interrelated because living is the husband's obligation in the household which aims to meet household needs, so not fulfilling the needs in the family can make the family less harmonious. Even so, there are different opinions from the people of Kemaduh village which state that the husband's inadequacy of living does not cause fights and the family remains harmonious.